2021
DOI: 10.3390/ijms22126457
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Intolerance of 5′-Truncated sgRNAs in CRISPR/Cas9 Enables Efficient Microbial Single-Base Genome Editing

Abstract: The CRISPR/Cas9 system has recently emerged as a useful gene-specific editing tool. However, this approach occasionally results in the digestion of both the DNA target and similar DNA sequences due to mismatch tolerance, which remains a significant drawback of current genome editing technologies. However, our study determined that even single-base mismatches between the target DNA and 5′-truncated sgRNAs inhibited target recognition. These results suggest that a 5′-truncated sgRNA/Cas9 complex could be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…Moreover, reportedly, the truncation of guide RNA reduces the off-target effect of Cas9 . It was recently reported that 2-nucleotide (nt) truncations at the 5′-end of a single molecular guide RNA (sgRNA) enhanced Cas9-mediated single-base substitution in the microbial genome . As in the case of Cas9, the 3′-end-truncated crRNA-Cpf1 complex can cause double-strand breaks in the target DNA even when 4–6 nt are truncated at the 3′-end of the canonical 23-nt spacer of the CRISPR/Cpf1 crRNA. , In this study, we systematically investigated the relationship between single-base mismatch tolerance and 3′-end nucleotide truncation in the CRISPR/Cpf1 crRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reportedly, the truncation of guide RNA reduces the off-target effect of Cas9 . It was recently reported that 2-nucleotide (nt) truncations at the 5′-end of a single molecular guide RNA (sgRNA) enhanced Cas9-mediated single-base substitution in the microbial genome . As in the case of Cas9, the 3′-end-truncated crRNA-Cpf1 complex can cause double-strand breaks in the target DNA even when 4–6 nt are truncated at the 3′-end of the canonical 23-nt spacer of the CRISPR/Cpf1 crRNA. , In this study, we systematically investigated the relationship between single-base mismatch tolerance and 3′-end nucleotide truncation in the CRISPR/Cpf1 crRNA.…”
Section: Introductionmentioning
confidence: 99%
“…CpG methylation at the promoters of genes is correlated with repression of those genes, , and dCas9 fused to DNMT3A can de novo methylate CpGs when directed to a promoter of interest and cause gene repression. In an initial screen in transfection-efficient HEK293FT cells, we directed a dCas9-DNMT3A fusion construct with 20 independent 17 bp truncated gRNAs to the ANTXR2 promoter and the associated CpG island to determine which targeted protospacer would generate the most repression of the gene (Figure A–C). Previous reports indicate that truncated gRNAs (less than the standard 20 bp) have low levels of off-target interactions , and are advantageous because even one mismatch in the target sequence greatly inhibits off-target binding. , Off-target analysis of the 20 designed truncated gRNAs in this study using Cas-OFFinder found that only four of the gRNAs designed have potential single mismatch off-target genomic sites (Table S1), suggesting that the truncated gRNAs used in this study have great potential for specific on-target binding. We found 4 gRNAs from the screen that repressed ANTXR2 48% or more, with gRNA-9 creating the most (70%) repression (Figure D).…”
Section: Resultsmentioning
confidence: 54%
“…Previous reports indicate that truncated gRNAs (less than the standard 20 bp) have low levels of off-target interactions 22,23 and are advantageous because even one mismatch in the target sequence greatly inhibits off-target binding. 22,24 Off-target analysis of the 20 designed truncated gRNAs in this study using Cas-OFFinder 25 found that only four of the gRNAs designed have potential single mismatch off-target genomic sites (Table S1), suggesting that the truncated gRNAs used in this study have great potential for specific on-target binding. We found 4 gRNAs from the screen that repressed ANTXR2 48% or more, with gRNA-9 creating the most (70%) repression (Figure 2D).…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…The sgRNA targets were located close to the N-terminus. Overall, they had only few predicted off-targets, which could be neglected due to their location in intergenic or intronic sequences with a minimum of three to four mismatches [ 34 ]. Finally, both proteins could be addressed due to the accuracy of the CRISPR/Cas9 method [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%